Pengaruh Tambahan Nano Fly Ash terhadap Kuat Tekan dan Modulus Elastisitas Beton - Hantoro Hantoro; Ilham Zaid Nabil; Ignatius Sudarsono (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2025)
Fly ash, the result of coal combustion, is commonly used as a cement substitution material. Its purpose is to reduce the use of cement and environmental pollution to create sustainable development. In addition, nanomaterials, currently known as materials with sizes in the range of 1 – 100 cm, are often applied in the construction world to improve the quality of concrete. Referring to these problems, this study was conducted to find out whether the use of nano fly ash as a substitution for some cement influences the strength of concrete. The methods used in this study are quantitative, experimental, and analytical, so accurate results are obtained based on the applicable parameters. The result of this study show that at 28 days, concrete with 20% nano fly ash is the optimum variation of all existing variations. The results are a compressive strength of 20,79 MPa and elastic modulus of 22563,84 MPa. Thus, the overall results suggest that using nano fly ash as a cement substitution can improve the quality of concrete.